An Efficient Method for In Vitro Shoot-Tip Culture and Sporophyte Production Using Selaginella martensii Spring Sporophyte - Kyungtae Park; Bo Kook Jang; Ha Min Lee; Ju Sung Cho; Cheol Hee Lee (Plants, 2020)
Selaginella martensii, an evergreen perennial fern that is native to South America and New Zealand, is named “frosty fern” because of its beautiful white-colored leaves and it is used as an ornamental plant. Efficient propagation methods for this species have not been developed. We aimed to develop an efficient propagation method for S. martensii through in vitro culture. We investigated culture conditions that are suitable for shoot-tip proliferation and growth. The optimum shoot-tip culture conditions were determined while using Murashige and Skoog (MS) medium (quarter, half, full, or double strength) and macronutrients (sucrose and two nitrogen sources) at various concentrations. In MS medium, the shoot tips formed a maximum of 6.77 nodes per explant, and each node formed two new shoot tips (i.e., 26 or 64 shoot tips). When using branching segments containing an angle meristem, the shoot-to-rhizophore formation ratio could be controlled by medium supplementation with plant-growth regulators. Sporophytes that were grown from shoot tips in vitro were acclimated in ex vitro soil conditions and successfully survived in the greenhouse. Numerous shoot tips could be obtained from in vitro-grown sporophytes and be proliferated ex vitro to produce a large number of plants. This method provides a way of shortening the time that is required for producing a large stock of S. martensii planting material.